Ionotropic Glutamate Receptors in the CNS - Jonas, Peter; Monyer, Hannah (Handbook of experimental pharmacology, 1999)
This volume provides an overview of glutamate receptors and their role in excitatory neurotransmission. It focusses on three aspects. First, it describes the functional, molecular, and pharmacological properties of glutamate receptors (AMPA, NMDA, and kainate receptors). Second, it gives a survey how these receptors are involved in synaptic transmission at different glutamatergic synapses in the mammalian CNS. Finally, it adresses how overactivation of glutamate receptors can lead to excitotoxic cell death, and emphasizes the importance of glutamate receptors as potential therapeutical targets. The chapters, written by leading scientists, give accurate summaries of facets that have emerged recently in this field. The book demonstrates the strength of a multidisciplinary approach involving physiology, pharmacology, and molecular biology. It will be useful for other scientists in and outside the field, lecturers and students at different educational levels